Implementation of Spiritual Education Quotient at Mambaus Sholihin Gresik Islamic Boarding School - ROMDLONI, MUKHAMMAD (Universitas Yudharta Pasuruan, 2025)
Pesantren as a means of tarbiyah in Islam also contributes positively to the development of individual SQ, as a learning center, pesantren provide a different educational atmosphere, not only emphasizing the development of IQ and EQ, but also focusing on the growth of SQ. This study aims to reveal (1) how the implementation of spiritual quotient education at the Mambaus Sholihin Gresik Islamic Boarding School, (2) how the impact of the Spiritual Quotient Education on the alumni of the Mambaus Sholihin Gresik Islamic Boarding School. This research uses qualitative descriptive with the type of case study. The data consists of primary, and secondary. Data collection (1) Observation, (2) Interviews and (3) Documentation. Informants are determined by techniques of (1) purposive sampling, (2) snowball sampling. Data analysis using Interactive models, namely: (1) data reduction, (2) data presentation, and (3) drawing and testing conclusions. Data validity testing is performed (1) triangulation of data sources, data, and time. (b) Documentation and References. The results of this study concluded; 1) Implementation of Spiritual Quotient Education (ESQ) carried out at the Mambaus Sholihin Gresik Islamic boarding school through several activities, namely: (1) Muhadlarah, which has a variety of activities including: a) Speech activities; b) Qiro'atul Qur'an activities and their translation; c) Storytelling activities (muthala'ah). (2) Qiro'atul Qur'an activities, which are carried out jointly with special trainers. and (3) Barzanji or Dziba'an activities, which is a tradition of chanting prayers to the Prophet Muhammad SAW carried out by the Nahdlatul Ulama community. 2) The impact of Spiritual Quotient education on alumni leads to several things, namely: a) Ability to adapt to various models and characters of society as in the alumni environment; b) The ability to maintain the relationship between God and His servants.